Dada'S Useless Present - Nalini Sorensen; Allen Shaw. (Chennai : Karaditales company Pvt. Ltd., 2020)
Dada may be celebrating his 82nd birthday but he still considers himself spry, until a seemingly thoughtful gift from his son tells him otherwise.
Dada'S Useless Present by Nalini Sorensen.
Keywords: Children Picture books; Colors book